Principles and Business Improvement Initiatives of Lean Relates to Environmental Management System - A. P., Puvanasvaran; Kerk, Swee Tian; Muhammad, Mohd Razali (IEEE International Technology Management Conferance, 2011)
Lean and Environmental Management System (EMS) are widely appreciated by organizations in improving business efficiency and productivity. The distinct systems have worked towards the enhancement of business capabilities, reducing production costs and meeting ISO standards. This paper analyzes these two systems and provides an understanding of how these processes have contributed in improving business efficiencies. Past research studies have revealed that there are wide ranging possibilities and scope of expanding the application potential of these systems to provide even better business models. The research study aims to provide an understanding of the individual systems and then goes on to explore the possibilities of integrating the two models to provide an effective approach to achieving organizational efficiency.